Языковые интересы и потребности студентов (Heteroglossia – studia kulturoznawczo-filologiczne, 2017)
The article presents the analysis of linguistic needs of students of the University of Economy in Bydgoszcz, Poland. The article is coauthored and is devoted to the issue of language interest and needs of students. This topic is of particular importance in the context of developing the processes of globalization, including the educational sphere. The thematic justification being revealed, the importance of the language skills attained by students is highlighted. To this end the students survey was carried out with the overall results indicating high interest among the young in acquiring an additional foreign language in the University. The authors analyze the findings of the conducted questionnaire and determine the prospects for development of certain aspects of foreign languages teaching in the present paper. The article highlights possible practical use of the findings by means of adjusting the existing curricular, arrangement of culture parties for international students, etc.